App to guide nurses on the assessment and treatment of complex surgical wounds (Revista Contexto & Saúde, 2025)
Wound treatments have advanced considerably with the expansion of therapeutic possibilities, treatment techniques and technological innovations for the care of skin lesions. This study aims at developing a mobile app to guide nurses in the assessment and treatment of complex surgical wounds. This is a methodological and descriptive study with a qualitative approach developed in a High-Complexity Oncology Center from the state of Pará. It was developed in two stages: initially, by identifying the target audience's main needs through semi-structured interviews that were analyzed following Bardin's method and using the IRAMUTEQ software. The second stage consisted in the technological production itself, according to Contextualized Instructional Design (analysis, design and development). The interviews with the participants supported and justified creating the “Pense Feridas” (“Think Wounds”) app. Aiming at good usability, the following topics were included on the main screen: concepts and classifications, complications, wound assessment, updates and references. These categories present secondary screens with pertinent and updated information on each topic. In addition, the software features a “Surgical wounds” icon where the professionals can add patient and wound information to indicate the best care standard, including coverage and dressing changes. This study made it possible to produce an app that is sensitive to the reality of nurses who deal with the assessment and treatment of patients with complex surgical wounds every day. Its implementation may favor systematic care recording and care continuity.
Keywords: Nursing-Care; Surgical-Wound; Technology